2010
DOI: 10.1242/dev.043257
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the organization of dorsal spinal cord pathways from an evolutionarily conserved raldh2 intronic enhancer

Abstract: SUMMARYComparative studies of the tetrapod raldh2 (aldh1a2) gene, which encodes a retinoic acid (RA) synthesis enzyme, have led to the identification of a dorsal spinal cord enhancer. Enhancer activity is directed dorsally to the roof plate and dorsal-most (dI1) interneurons through predicted Tcf-and Cdx-homeodomain binding sites and is repressed ventrally via predicted Tgif homeobox and ventral Lim-homeodomain binding sites. Raldh2 and Math1/Cath1 expression in mouse and chicken highlights a novel, transient,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 68 publications
3
38
0
3
Order By: Relevance
“…A similar picture is emerging for TCFs and AP-1, where Wnt and mitogenic signals converge (Bottomly et al, 2010;Domenzain-Reyna et al, 2009;Nateri, Spencer-Dene, and Behrens, 2005). Other examples are Cdx proteins and TCFs, where Cdx1 associates with LEF1 (Beland et al, 2004), TCF4 binding to chromatin is reduced a Cdx2 mutant cells (Verzi et al, 2010) and functional TCF and Cdx binding sites are found in close proximity in a chick WRE (Castillo et al, 2010).…”
Section: Colocalization Of Tcfs With Other Tfsmentioning
confidence: 83%
“…A similar picture is emerging for TCFs and AP-1, where Wnt and mitogenic signals converge (Bottomly et al, 2010;Domenzain-Reyna et al, 2009;Nateri, Spencer-Dene, and Behrens, 2005). Other examples are Cdx proteins and TCFs, where Cdx1 associates with LEF1 (Beland et al, 2004), TCF4 binding to chromatin is reduced a Cdx2 mutant cells (Verzi et al, 2010) and functional TCF and Cdx binding sites are found in close proximity in a chick WRE (Castillo et al, 2010).…”
Section: Colocalization Of Tcfs With Other Tfsmentioning
confidence: 83%
“…Accordingly, it was reported an evolutionarily conserved daldh2 intronic enhancer in the frog, mouse, and chicken, being also involved in the formation of the neural tube throughout vertebrate species [7]. This evolutionary conservation of the enzyme playing a role in shaping the neural tube is essentially related to the evolutionary conservation of the neural networks for the diagonalsequence QL.…”
Section: Evolutionarily Preserved Neural Network For Qlmentioning
confidence: 97%
“…Furthermore, Raldh2, a RA synthetic enzyme is the first Raldh to appear in mouse and chick embryos, and overlaps with sites of RA signaling (Zhao et al, 1996;Niederreither et al, 1997;Moss et al, 1998;Ulven et al, 2000;Xavier-Neto et al, 2000;Blentic et al, 2003;Lin et al, 2003). Recently, a conserved intronic enhancer that drives raldh2 expression in the RP and dorsal interneurons of frog, mouse, and chicken was identified (Castillo et al, 2010). Moreover, both CRAPB and RA receptor a (RAR a) were also detected in emigrating and migrating NC cells and in NC-derived DRG, SG and enteric ganglia (Ruberte et al, 1991).…”
Section: The Segregation Between Nc and Rpmentioning
confidence: 99%